ANALISIS KEBUTUHAN KECEPATAN BANDWIDTH GAME ONLINE (Free fire, Mobile Legends, Pubg mobile): The Analysis of Bandwidth Speed Needs for Online Games (Free fire, Mobile Legends, Pubg mobile) - Ahmad Tantoni; Mohammad Taufan Asri Zaen; Khairul Imtihan (Jurnal Informatika dan Rekayasa Elektronik, 2019)
Online Game users continue to grow from year to year and therefore internet service providers (ISPs) must provide stable and fast internet quality. The Bandwidth requirements of online Games must be supported by internet networks that support the speed and stability of the internet connection. When using online Games sometimes the connection is bad, so it makes a condition called lagging. Then make the online Game avatars do not move or the traffic is stuck. This makes online Game players lose to enemies because, when the online Game avatar is not moving it will be easy for the enemy to shoot dead. Based on this, an analysis of the research needs of online Game Bandwidth speed needs to be done so, that internet service providers (ISPs) can divide how much speed or Bandwidth to the Game needs so, that online Game users feel comfortable, safe without feeling any slow or lagging conditions. This study tested by 3 Games, such as Free fire, Mobile Legends, and Pubg mobile. Each Game uses graphics and image quality which is being tested for 10 minutes. The results of this study shows that all of the three Games requires a stable internet connection for Uploading and Downloading.